Militia amoris in akkadian, greco-roman, and sanskrit literature - Morales Harley, Roberto (2023)
The paper analyzes the topic of the militia amoris under its variants of love as was, love against war, and the triumph of love. It works with a corpus of 29 passages, taken from Akkadian love poetry (The Faithful Lover, ca. 2000-1500 BCE), Latin love elegy (Tibullus’ Elegies Propertius’ Elegies, Ovid’s Amores; ca. 50-1 BCE), and Sanskrit love lyric (Bhartṛhari’s Passion, ca. s. IV CE; Amaru’s Hundred Poems, ca. s. VII CE; and Bilhaṇa’s The Fifty Stanzas of a Thief, ca. s. XI CE). In conclusion, it proposes the possibility of an Akkadian influence in the Greco-Roman version of the topic, as well as the possibility of subsequent influence of the latter in the love poetry in Sanskrit language.